Public policies against criminal assets in mexico: challenges and opportunities from the north border states - Estrada, Pedro R. Torres (Crime, law and social change, 2021)
Given its vast border with the United States, Mexico is a strategic trade and economic development region, which creates significant challenges in combating crime and violence. In recent years, Mexico´s federal and state governments have focused their efforts on the development of strategies to combat and weaken the criminal structures operating in the country by using legal instruments such as seizure, abandonment, and extinction of domain. This study seeks to identify the challenges faced by the states of Baja California, Chihuahua, Coahuila, Nuevo Leon, Sonora, and Tamaulipas in their efforts to combat crime through the collection of primary and secondary data and interviews with key actors. Mexico faces major challenges in the development of public policies to fortify the legal precepts of extinction of domain, in addition to fostering institutional links with the Financial and Patrimonial Intelligence Units of Mexico's northern Border States. There are few studies about subnational efforts for asset forfeiture as a policy instrument against criminal elements in developing countries. The Mexican case presents important subnational efforts to improve security strategies that may provide guidance for other subnational governments or regions that may be facing similar challenges or are pursuing parallel initiatives.